Do Politicians Outside the United States Also Think Voters Are More Conservative than They Really Are? – CORRIGENDUM. - PILET, JEAN-BENOIT; SHEFFER, LIOR; HELFER, LUZIA; VARONE, FREDERIC; VLIEGENTHART, RENS; WALGRAVE, STEFAAN (American Political Science Review, 2026)
This article focuses on correcting an error in a previously published figure related to the distribution of politicians' conservative bias by country. The original Figure 3 incorrectly displayed histograms of individual statements rather than the intended average inaccuracy of politicians' estimations of public opinion across all statements. The corrected figure now accurately reflects the average distribution as described in the original caption. The replication materials have been updated accordingly, and the authors acknowledge the contribution of a Harvard University researcher who identified the mistake.